FAKTOR-FAKTOR YANG MEMPENGARUHI KUNJUNGAN BALITA DALAM PEMBERIAN IMUNISASI CAMPAK DI POSYANDU DESA PERTIBI TEMBE KEC.MEREK TAHUN 2019 - Srilina Pinem (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2020)
Measles immunization is an attempt to provide immunity to infants and children by introducing vaccines into the body so that the body makes anti-substances to prevent measles. Measles immunization is important to give because the rate of transmission of measles infection is very high, which often causes outbreaks. Measles CFR in Indonesia is 3%. The measles immunization program indicator used is Universal Child Immunization (UCI), which is 100% measles immunization coverage. This research is analytic with cross sectional design. The purpose of this study was to determine the factors that influence the visit of children under five in giving measles immunization in Posyandu Pertibi Tembe Village, Karo District, 2019. The population is all mothers who have children under five in Posyandu Tembe Village, Tembe Village, Karo District. The sample is a portion of mothers who have 45 children under five. Data analysis is done by univariate, bivariate. A proportion of those who did not have measles immunization found 28.9%. The highest proportion of mothers by age at umur 30 years is 75.6%, high school education 38.9%, housewives 38.9%, parity ≤ 2 68.9%, good knowledge 68.9%, good attitude 94, 4%, there is an effect (fever) 64.4% and a distance of 3-5 km 40%. The results of the bivariate analysis found 4 variables that had a significant relationship with measles immunization, namely maternal age (p = 0.005; RP = 2.649), maternal education (p = 0.000; RP = 3.595), parity (p = 0.007; RP = 2.583) , mother's knowledge (p = 0,000; RP = 4,183). It is expected that Posyandu Desa Pertibi Desa Kecamatan District will improve health services in its working area, especially in terms of promotion and prevention through counseling about the importance of immunization in order to increase community knowledge about immunization.